Genetic Homogenity of Commerson’s Anchovy (Stolephorus commersonnii) in Segara Anakan Cilacap Central Java Inferred from PCR-RFLP Markers - Nuryanto, Agus; Dewi, Rani Eva; Pramono, Hendro (Biogenesis: Jurnal Ilmiah Biologi, 2019)
Commerson’s anchovy (Stolephorus commersonnii) is a small pelagic fish that live in a group and its existence is very abundant in Segara Anakan Cilacap. This anchovy is widely consumed by communities live around Segara Anakan. This leads to a high exploitation rate. Exploited populations generally have low genetic diversity. This study aims to evaluate genetic diversity of commerson’s anchovy population in Segara Anakan Cilacap inferred from PCR-RFLP of the cytochrome c oxidase 1 (CO1) gene. This study was conducted from January to April 2018 and used survey method by applying random sampling. As many as 30 samples of anchovy were taken. Genomic mtDNA was isolated using modified Chelex method. Partial sequences of the COI gene were amplified using a pair forward commercially available primer. The lengths of 650 base pair of the PCR products were digested with four restriction enzymes. The HindIII enzyme produces PCR-RFLP fragment with the size of 416 bp and 234 bp lengths, VspI produces 435 bp and 214 bp, CO1-TaqI produces 556 bp and 94 bp and RsaI produces 319 bp, 183 bp, and 148 bp fragments, respectively. The PCR-RFLP fragments were obtained from all samples but they produced uniform band pattern for all 30 anchovy individuals. These results indicated that the anchovy population in Segara Anakan Cilacap has monomorphic allele for all PCR-RFLP markers. Hence, it can be concluded that genetic homogenity was observed on anchovy population in Segara Anakan Cilacap as inferred from PCR-RFLP COI gene.